ANALISIS IMPLEMENTASI SOCIAL-EMOTIONAL LEARNING PADA PESERTA DIDIK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI - Rizky Sania; Ngabiyanto; Wadiyo; Tri Joko Raharjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Social-Emotional Learning (SEL) is the process of developing skills that enable individuals to understand and manage their emotions, build positive relationships, and make responsible decisions. SEL includes five core competencies: self- awareness, self-management, social awareness, relational skills, and responsible decision making (CASEL, 2020). The method used in this research is a literature review. The data source was taken by reviewing articles containing research results on Social-Emotional learning in inclusive schools which came from 2 main sources, namely Google Scholar and Publish or Perish. The aim of this research is to analyze the implementation of SEL in PDBK in inclusive schools. The subjects of this research are low class GDPK in Inclusive Schools. The results of this research show that there are still many students with special needs who do not receive SEL intervention at school.